SEARS AND ZEMANSKY'S UNIVERSITY PHYSICS WITH MODERN PHYSICS TECHNOLOGY UPDATE - Freedman Roger A; Young Hugh D (Pearson, 2014)
UNITS, PHYSICAL QUANTITIES AND VECTORS MOTION ALONG A STRAIGHT LINE MOTION IN 2 OR 3 DIMENSIONS NEWTON'S LAWS OF MOTION APPLYING NEWTON'S LAWS
UNITS, PHYSICAL QUANTITIES AND VECTORS MOTION ALONG A STRAIGHT LINE MOTION IN 2 OR 3 DIMENSIONS NEWTON'S LAWS OF MOTION APPLYING NEWTON'S LAWS